Magnetocaloric effect and slow magnetic relaxation in peroxide-assisted tetranuclear lanthanide assemblies. Issue 19 (22nd August 2022) - Kumar, Pawan; Flores Gonzalez, Jessica; Sahu, Prem Prakash; Ahmed, Naushad; Acharya, Joydev; Kumar, Vierandra; Cador, Olivier; Pointillart, Fabrice; Singh, Saurabh Kumar; Chandrasekhar, Vadapalli
Abstract : Investigation of a series of rare peroxide-assisted tetranuclear lanthanide assemblies revealed both significant magnetocaloric effect and slow magnetic relaxation. Abstract : The synthesis, structure and magnetism of tetranuclear complexes, [Ln4 (LH2 )2 (η 1 -Piv)2 (η 2 -Piv)2 (μ3 -O2 )2 (H2 O)2 ]·2MeOH (1, Ln = Gd III ; 2, Ln = Tb III ; 3, Ln = Dy III ; and 4, Ln = Er III ) (LH4 = 6-((bis(2-hydroxyethyl)amino)- N ′-(2-hydroxybenzylidene)picolinohydrazide) (piv = pivalate ion) are reported. Interestingly, the formation of these tetranuclear assemblies is assisted by two side-on coordinating peroxide ligands which bind in a μ3 -η 2 :η 2 :η 2 fashion. DC magnetic behaviour revealed the existence of a dominating but weak intramolecular antiferromagnetic interaction in the cases of 1, 2, and 4, while a small structural change in complex 3 turns this into a ferromagnetic interaction. We have investigated the magnetothermal behaviour of 1 which shows a magnetocaloric effect with the value of maximum entropy change of −Δ S m = 33.60 J K −1 kg −1 at 4 K (Δ H = 13–0 T). This is close to the calculated value of 36.45 J K −1 kg −1 . The ac magnetic susceptibility study confirms zero-field out-of-phase magnetic susceptibility signals only for 3 which get well resolved on the application of a 1 kOe dc magnetic field. The energy barrier for the Orbach process of spin reversal was found to be 23 K ( τ 0 = 9 × 10 −7 s). We also report detailed theoretical studies to rationalize and understand the observed magnetic behaviour.